(untitled) (Altifani : Jurnal Pengabdian Masyarakat Ushuluddin, Adab, dan Dakwah, 2025)
The holy month of Ramadan is considered an opportune moment for the performance of good deeds. Muslims engage in a greater number of acts of worship during the month of Ramadan than at any other time. Consequently, this period is considered optimal for a Da’i to disseminate the tenets of Islam. It is through this da’wah that the formation of piety in an individual is aspired to be achieved. The present research is classified as qualitative, incorporating two approaches: the field study approach and the autoethnographic approach. This approach is employed because, in addition to the author going directly to the field, the author as a researcher is also the object under study, because the author himself delivers da’wah messages. The findings of this study demonstrate that, in addition to mau’idhah hasanah, wisdom constitutes an approach adopted by the author in their preaching. This approach is employed to adapt to the mad’unya. For instance, in a discourse directed towards mothers, the author employs the theme of maintaining one’s verbal conduct. In the context of delivering a sermon to students, the author employs the theme of the significance of manners and knowledge. In the context of tarawih prayer congregations during Ramadan, the author employed the theme of piety as the underlying purpose of fasting. In the context of halal bi halal events, the author employs the theme of maintaining silaturrahim. The dissemination of da’wah messages that are tailored to the mad’unya is anticipated for the author as a preacher, with the objective of fostering piety in individuals according to their specific needs.